PSYCHOLOGICAL FIRST AID TRAINING UNTUK MENINGKATKAN MENTAL HEALTH AWARENESS PADA REMAJA DI ERA PANDEMI COVID-19 - Edmawati, Mahmuddah Dewi; Susanto, Bambang; Maulana, Muhammad Arief; Kumalasari, Rita (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. Growing up in a recession, Gen Z is given more protection, so they are often easily anxious when things don't go the way they want. For this reason, Gen Z needs to have good mental awareness in order to be able to avoid stress and depression in facing life's challenges. This community service aims to increase mental health awareness in adolescents in the era of the covid-19 pandemic. Psychological First Aid (PFA) training participants are youth youth in Kalikatir Hamlet RT 01/ RW 06, Nambangan, Selogiri, Wonogiri. The trainees are Gen Z teenagers, born in 1995-2010. Through Psychological First Aid Training, it is one solution to increase mental health awareness in Gen Z youth in the era of the COVID-19 pandemic. Psychological First Aid (PFA) is a method to help someone in distress so that they feel calm and supported, in order to better cope with their challenges or problems. PFA itself is done by means of peer tutors or peer counselors. The training participants are given the basics of PFA which they will then practice to be able to become good and skilled helpers when helping friends, family or communities who are facing psychological problems. The basis of PFA is caring for someone in distress by showing empathy. PFA has 3 main principles, namely Look, Listen, and Link. Based on the results of the Wilcoxon test, the Z count result is -1.814 with a significance of 0.036. The significance value of Asymp.sig (2-tailed) 0.036 is smaller than 0.05, which means that there is a difference in the average mental health awareness score between before and after being given Psychological First Aid Training so that Psychological First Aid Training is effective for increasing mental health awareness among adolescents in the era of the covid-19 pandemic. Abstrak. Tumbuh di era resesi, membuat Gen Z diberikan perlindungan lebih, sehingga mereka seringkali mudah merasa cemas bila keadaan tidak berjalan sesuai yang mereka inginkan. Untuk itulah gen Z ini perlu memiliki kesadaran mental yang baik agar mampu menghindari stress maupun depresi dalam menghadapi tantangan kehidupannya. Pengabdian masyarakat ini bertujuan untuk meningkatan mental health awarness pada remaja di era pandemi covid-19. Peserta pelatihan Psychological First Aid (PFA) adalah remaja karangtaruna di Dusun Kalikatir RT 01/ RW 06, Nambangan, Selogiri, Wonogiri. Peserta pelatihan adalah remaja gen Z yaitu kelahiran 1995-2010. Melalui Psychological First Aid Training merupakan salah satu solusi untuk meningkatkan mental health awareness pada remaja gen Z di era pandemi covid-19. Psychological First Aid (PFA) adalah sebuah metode untuk membantu seseorang dalam kondisi distres agar mereka merasa tenang dan didukung, guna mengatasi tantangan atau permasalahan mereka dengan lebih baik. PFA sendiri dilakukan dengan cara tutor teman sebaya atau konselor teman sebaya. Peserta pelatihan diberikan dasar PFA yang kemudian akan mereka praktikkan untuk bisa menjadi penolong yang baik dan terampil ketika membantu teman, keluarga atau masyarakat yang menghadapi permasalahan psikologis. Dasar dari PFA adalah kepedulian terhadap sesorang dalam kondisi distres dengan menunjukkan empati. PFA memiliki 3 prinsip utama yaitu Look (Lihat), Listen (Dengarkan), dan Link (Hubungkan). Berdasarkan hasil pengujian wilcoxon diperoleh hasil Z hitung sebesar sebesar -1,814 dengan signifikansi sebesar 0,036. Nilai signifikansi Asymp.sig (2-tailed) 0,036 lebih kecil dari 0,05 berarti ada perbedaan rata-rata skor mental health awareness antara sebelum dan sesudah diberikan Pelatihan Psychological First Aid sehingga Pelatihan Psychological First Aid efektif untuk meningkatkan mental health awareness pada remaja di era pandemi covid-19.